Shaping Porous Materials for Hydrogen Storage Applications: A Review - Ren, Jianwei; North, Brian C. (Journal of Technology Innovations in Renewable Energy, 2014)
Development of safe and effective hydrogen storage systems becomes a critical factor for further implementation of fuel cell and hydrogen technologies. Among new approaches aimed at improving the performance of such systems, the concept of porous materials-based adsorptive hydrogen storage is now considered as a long-term solution due to the reversibility, good kinetics and absence of thermal management issues. However, the low packing densities associated with the porous materials such as carbon structure materials, zeolites, metal-organic frameworks lead to the compromised volumetric capacity, potential pipe contaminations and difficulties in handling, when introducing the powdered adsorbents into hydrogen storage systems. Some efforts have been devoted to solve this problem by shaping the porous materials into beads, pellets or monoliths and achieve higher storage densities at more moderate temperatures and pressures. This review will firstly state the essential properties of shaped structures for hydrogen adsorption, and then highlight the recent attributes that potentially can be utilized to shape porous materials into specific configurations for hydrogen storage applications. Later, several testing techniques on structured porous material will be also discussed.